The Implications of Knowledge Transfer for Universities in General and for Arts and Humanities Subjects in Particular - Shepherd, David; Parrott, Helen (My University, 2008)
Knowledge Transfer (KT) is an increasingly high-profile part of government policy in the United Kingdom, and this interactive seminar aims to explore whether KT is a uniquely UK concept. It will begin with an introduction to Knowledge Transfer in the context of higher education in the UK, with particular reference to the arts and humanities and the University of Sheffield experience. Participants will be invited to discuss and provide feedback on several key questions, including: * How, if at all, is the UK version of Knowledge Transfer understood a) in your country, b) in your institution, c) by your subject area, and d) by you? * What are the implications of this understanding in an increasingly global world? To help participants prepare for the seminar, the presenters have provided three different working definitions of Knowledge Transfer drawn from UK sources: 1. Activities that are concerned with the generation, use, application, and exploitation of knowledge and other university capabilities outside academic environments (University of Sheffield, 2007). 2. Government support for the research base aims to increase the contribution made to improving exploitation of the research base to meet national economic and public service objectives. The Research Councils believe that the maximum benefit is derived from their investments. They run a number of initiatives that aim to encourage the flow of ideas, trained people, and knowledge to potential users and beneficiaries in business, in government, and in the voluntary and charitable sectors. These (knowledge transfer) activities can be placed under four broad headings: a) cooperation in education and training at masters and doctoral level; b) people and knowledge flow; c) collaborative research with users; and d) commercialization, including IP exploitation and entrepreneurial activities (Research Councils UK, 2008). 3. To exploit fully the new knowledge and learning that is generated in higher education Institutions, it has to be applied to areas of life where it can make a difference (Arts and Humanities Research Council, 2007).
Keywords: International and Comparative; International and Comparative; Entrepeneurial University